The concept and structural elements of the system of personal empowerment rights of employees - I. M. Kravchenko (Bulletin of Kharkiv National University of Internal Affairs)
The article considers the problem of defining the system of personal non-property rights of an employee, as a set of its individual structural basic elements in the system of personal non-property benefits of an individual, and in the general system of human rights. The essence and content of any social, legal phenomena, which are the personal non-property rights of employees, as relevant legal values, can be fully revealed only thanks to the study of objective signs characteristic of these rights. When studying the current issues of employees’ personal rights, it is extremely important to determine their structure as a certain systemic formation and a separate group in the general system of labour rights which would reflect and ensure their internal differentiation and external unity. Due to the fact that the personal rights of a person are a separate type of subjective rights (they belong to the category of intangible goods), their features are the absence of direct property content and an inseparable connection with the personality of their bearer. At the same time, in an objective sense, personal non-property rights are undeniably a complex legal institution that forms the norms of various branches of public and private law (constitutional, criminal, administrative, environmental, civil, family, housing, labor, etc.). Based on the analysis of the provisions of national and prospective legislation, as well as the achievements of scientific thought, the article provides a legal description of the concept of the system, structure and elements of the system of personal non-property rights of an employee in connection with the performance of his/her employment duties. The issue of the possibility of regulatory definition and consolidation of the system and classification of personal non-property rights of employees in the course of their employment functions has been investigated. The scientific novelty of the publication is that the issue of systematization and/or classification of the employee's personal non-property rights has been comprehensively researched, taking into account the classes (types) of their types, in accordance with the requirements of national civil and labor legislation and according to scientific research.